TAMAILA IN TIME FRAME: A QUALITATIVE STUDY OF THE DYNAMICS OF COMMUNITY LIFE (2003-2020) - Palai, Nur Adinda; Manay, Helman; Malae, Andris K. (Satmata: Journal of Historical Education Studies, 2025)
Decentralization and regional autonomy in Indonesia, especially through Law Number 32 of 2004, have changed the position of villages into fully autonomous administrative units, giving rise to significant dynamics at the local level. This study aims to analyze the social, economic, and cultural changes in the community of Tamaila Village, Tolangohula District, Gorontalo Regency, from 2003 to 2020. This period is crucial because it coincides with the implementation of the policy which directly affects village life. This study uses a descriptive approach to present a comprehensive and detailed picture of the changes that have occurred, supported by interviews and secondary data analysis related to the demographic, social, and economic conditions of the village. This approach allows researchers to capture narratives, subjective experiences, and the meaning of change from the perspective of residents. The results of the study show that the Establishment of Tamaila Village in 2003 was fundamentally a direct response to the demands and urgent needs of the community for more effective and equitable government services, especially because the previous area was too large to hinder the reach of administration and development.